Cognitive training in neurodegenerative diseases： a way to boost neuroprotective molecules - Angelucci, Francesco; Caltagirone, Carlo; Costa, Alberto (Neural regeneration research, 2015)
Neurotrophins,and growth factors in general,are proteins which exert many actions in central nervous system neurons.Neurotrophins promote the survival and neuronal function of neurons and exert neuroprotective effects in pathological models of neurodegenerative diseases.In humans several clinical trials based on the use of these proteins have been carried out. Among them, it is worth to mention gene ther- apy especially in Parkinson＇s disease （PD） （Kordower and Bjorklund, 2013）, and a series of experiments using vectors capable of carrying neurotrophins in the selected target re- gion where they can exert their beneficial action （Ghosh et al., 2014）.